Biphasic pulses enhance bleomycin efficacy in a spontaneous canine genital tumor model of chemoresistance: Sticker sarcoma - Spugnini , Enrico P (BioMed Central, 2008)
Sticker's sarcoma (also known as transmissible venereal tumor) is a horizontally transmitted neoplasm of the dog, that is passed with coitus. It is a locally aggressive tumor with a low tendency to metastatic spread. The most common locations are the genitals, the nose, the perianal area. Standard treatment consists with chemotherapy with vincristine, however other therapies such as, cryotherapy, immunotherapy or, in selected cases, radiation therapy, have been reported. In this article we describe the outcome of a small cohort of canine patients, with chemotherapy resistant transmissible venereal tumor (TVT), treated with bleomycin selectively driven by trains of biphasic pulses (electrochemotherapy). Three canine patients, with refractory TVT, entered the study and received two sessions of ECT under sedation. The pets had local injection of bleomycin at the concentration of 1.5 mg/ml and five minutes after the chemotherapy, trains of 8 biphasic electric pulses lasting 50 + 50 μs each, with 1 ms interpulse intervals, were delivered by means of modified caliper or, for difficult districts, through paired needle electrode. All the patients responded to the treatment and are still in remission at different times. Electrochemotherapy appears as a safe and efficacious modality for the treatment of TVT and warrants further investigations.